New Signal Functions to Measure the Ability of Health Facilities to Provide Routine and Emergency Newborn Care - Gabrysch, Sabine; Civitelli, Giulia; Edmond, Karen M.; Mathai, Matthews; Ali, Moazzam; Bhutta, Zulfiqar A.; Campbell, Oona M. R. (PLOS Medicine, 2012)
Based upon an expert survey and consensus method, Sabine Gabrysch and colleagues recommend new signal functions to monitor and track facilities' provision of routine and emergency newborn care.